THE INFLUENCE OF BRAND IMAGE, PRODUCT VARIETY, AND PRICING STRATEGY ON PURCHASE DECISION OF EYELASH EXTENSION AT LASHTHETIQUE MANADO (STUDY ON LASHTHETIQUE CUSTOMERS) - Ivany Anastacia Mewoh; S. L. H. V. J Lapian; Emilia M. Gunawan (Universitas Sam Ratulangi, 2023)
The needs and desires of a dynamically moving market change rapidly and continuously, makes a company need to find a good strategy to meet the market wants and needs. The purpose of this research is to analyze the influence of brand image, product variety, and pricing strategy on purchase decision of eyelash extension service made by customers at Lashthetique partially and simultaneously. This research conducted using quantitative method with saturation sampling method, which use all of the population for the sample totaling 74 sample due to a small amount of population. The collected data from questionnaires with likert scale method was processed in SPSS 26 resulting brand image, product variety and pricing strategy are influencing purchase decision simultaneously, brand image and product variety does not influence purchase decision partially, and pricing strategy influence purchase decision partially. In this research, a brand image does not play an important role because a new running business still have less customer experience and perceived, while product variety and pricing strategy will be considered by customer to match their need and wants based on their purchasing power. Keywords: purchase decision, brand image, product variety, pricing strategy